POTENCY OF SOURSOP LEAF (ANNONA MURICATA L.) DECOCTION WATER AS A TRIGGER FOR MICE (MUS MUSCULLUS) LIVER CELL REGENERATION MARKED BY CYCLIN D1 EXPRESSION DUE TO RHODAMINE B INFECTION - Wally, Pramita (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
Soursop leaf (Annona muricata L.) is one of the plants that contains chemical compounds such as acetogenins, flavonoids, saponins, tannins, triterpenoids and glycosides where this group of chemical compounds has the potential as antioxidants to ward off free radicals. This study aimed to determine the effect of soursop leaf decoction in regenerating liver cells of male mice of the Balb/C strain induced by rhodamine B through the expression of cyclin D1. The 25 mice were divided into 5 groups, namely group I was given standard feed, group II was given standard feed and rhodamine B 0.4 mg/ml, groups III, IV and V were given standard feed, rhodamine B 0.4 mg/ml, and water. soursop leaf decoction with doses of 3.64 mg/g BW, 7.28 mg/g BW, and 10.92 mg/g BW for each group. The treatment was carried out for 14 days by giving soursop leaf boiled water after rhodamine B induction for 7 days. The results showed that the boiled water of soursop leaves at a dose of 10.92 mg/g BW had a significant effect on reducing levels of SGOT and SGPT (p<0.05) and could regenerate mice liver cells through the expression of cyclin D1. Based on the results of the study, it can be concluded that the antioxidant content of soursop leaf boiled water can prevent liver cell damage in mice and increase cell regeneration power